2006
DOI: 10.1152/ajpcell.00003.2006
|View full text |Cite
|
Sign up to set email alerts
|

Bitter stimuli induce Ca2+ signaling and CCK release in enteroendocrine STC-1 cells: role of L-type voltage-sensitive Ca2+ channels

Abstract: We previously demonstrated the expression of bitter taste receptors of the type 2 family (T2R) and the ␣-subunits of the G protein gustducin (G␣ gust) in the rodent gastrointestinal (GI) tract and in GI endocrine cells. In this study, we characterized mechanisms of Ca 2ϩ fluxes induced by two distinct T2R ligands: denatonium benzoate (DB) and phenylthiocarbamide (PTC), in mouse enteroendocrine cell line STC-1. Both DB and PTC induced a marked increase in intracellular [Ca 2ϩ (3,13,19,60). Molecular sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
171
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(182 citation statements)
references
References 80 publications
9
171
1
1
Order By: Relevance
“…The L-type voltage-gated calcium channel blockers nimodipine and nifedipine have been previously shown to totally block the L-type voltage-gated channels activated by various stimuli in STC-1 cells in the same or even lower concentrations that used in this study [18,19,23,24]. Blocking the L-type voltage-gated calcium channels only partially (by 36%) reduced the AITC induced CCK release suggesting that voltage-gated calcium channels contribute to some extent to the calcium influx in response to AITC stimulation, yet the major proportion of the increased calcium levels is due to calcium influx via TRPA1.…”
Section: Discussionmentioning
confidence: 73%
“…The L-type voltage-gated calcium channel blockers nimodipine and nifedipine have been previously shown to totally block the L-type voltage-gated channels activated by various stimuli in STC-1 cells in the same or even lower concentrations that used in this study [18,19,23,24]. Blocking the L-type voltage-gated calcium channels only partially (by 36%) reduced the AITC induced CCK release suggesting that voltage-gated calcium channels contribute to some extent to the calcium influx in response to AITC stimulation, yet the major proportion of the increased calcium levels is due to calcium influx via TRPA1.…”
Section: Discussionmentioning
confidence: 73%
“…S3D). The noninnervated enteroendocrine cells release bioactive peptides rather than neurotransmitters in response to T2R activation (37,38). Despite these differences, the T2R/ gustducin/TrpM5-expressing epithelial cells in the different tissues are similar in extending microvillous processes to the top of the epithelium where the cells will have access to the luminal content of each particular organ.…”
Section: Discussionmentioning
confidence: 99%
“…The recent identification of taste receptors and their downstream signaling molecules in the GI mucosa suggests a role for these receptors in the functional detection of nutrients in the gut, which may in turn initiate a hormonal or neural cascade pathway (11). Taste receptors are also present in the tongue epithelium and consist of two G protein-coupled receptor families, T1R and T2R.…”
mentioning
confidence: 99%
“…The presence of multiple transcripts corresponding to specific bitter taste receptors has been demonstrated in the upper GI tract of rodents and in a mouse GI enteroendocrine cell line, STC-1 (17). It has been reported that the bitter agonists, phenylthiocarbamide (PTC) and denatonium benzoate (DB), induce the release of cholecystokinin (CCK) and GLP-1 from STC-1 cells (11,18).…”
mentioning
confidence: 99%